Analisis dan Optimalisasi Kinerja Jaringan RT/RW Net Berbasis QoS TIPHON di Desa Sampe - Junia Suma Pintari; I Made Widiarta; Yunanri W; dimas wiryatari (Universitas Komputer Indonesia, 2026)
ABSTRACT – The RT/RW Net network in Sampe Village serves as an internet access medium for the community with a dynamic number of users. However, it often experiences a decline in service quality, especially during peak traffic periods, characterized by low throughput and high delay, jitter, and packet loss due to suboptimal bandwidth management. This research aims to evaluate the performance of the RT/RW Net network in Sampe Village before and after optimization using the Peer Connection Queue (PCQ) method on a MikroTik router, based on Quality of Service (QoS) parameters. The research method employed is quantitative with an experimental approach, measuring QoS under two conditions: morning (low traffic) and evening (high traffic). The analyzed parameters include throughput, delay, jitter, and packet loss, evaluated against TIPHON standards. The comparison of network performance before and after optimization demonstrates that the PCQ method is effective in fairly distributing bandwidth and maintaining network stability, particularly during high-traffic conditions. Thus, PCQ is a viable solution for optimizing RT/RW Net networks with dynamic user characteristics. Keywords – RT/RW Net, Peer Connection Queue, MikroTik, Quality of Service, TIPHON.